OPTIMIZATION OF CUTTING DIRECTION PARAMETERS FOR A CNC MILLING MACHINING PROCESS POCKET ON STRUCTURE AND SURFACE ROUGHNESS ON POSTEP MOTORCYCLE SPARE PARTS - Habiby, M. Nuril Anwar; Istianto, Puspo Vandy; Fahmi, Muhammad (International Journal of Mechanical Engineering Technologies and Applications, 2023)
CNC Milling machine is a machine that is widely used for the manufacture of a component. Product quality will be related to product selling value and consumer satisfaction, therefore the best parameters must be known in order to produce quality products. This study aims to determine the effect of the cutting direction on the structure and surface roughness of the pocket feeding CNC Milling machining process. Experimental methods are used to improve the quality of products produced by CNC Milling machines. The parameters used in this study are variations of spindle speed 500 rpm, 1900 rpm, and 5000 rpm, as well as variations of cutting direction, namely one way and zig-zag. The tests carried out are in the form of surface roughness testing, micro-structure observations, and macro-structures. The data analysis technique used is descriptive statistics. The results obtained are the use of the cutting direction parameter affects the quality of the resulting product in the form of structure and surface roughness. The zig-zag cutting direction parameter with spindle speed 5000 rpm obtained the lowest average surface roughness value of 0.87 Î¼m, while the one way cutting direction with spindle speed 500 rpm obtained the highest average roughness value of 2,84 Î¼m. In conclusion, using a higher spindle speed will result in a lower roughness value, while the zig-zag cutting direction produces a lower roughness value and a more even surface structure compared to one way cutting direction.